Advanced Semiconductor–Biochar Engineering of TiO2/Biochar Photocatalysts for Efficient Tartrazine Dye Degradation: Mechanistic Insights and UV–Vis Spectrophotometric Evaluation - Husein, Saddam; Puspita, Anindia; Tutik; Octonariz, Vito Zhafran (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2026)
This study aimed to evaluate the effectiveness of TiO₂/Biochar photocatalysts for tartrazine dye degradation using UV–Vis spectrophotometric analysis. The experiments were conducted using various catalyst dosages and treatment conditions including UV–Vis irradiation, UV-A irradiation, and dark adsorption. The results showed that the optimum catalyst dosage was 0.5 g with a degradation efficiency of 73%, while UV–Vis irradiation produced the highest degradation activity compared to other treatments. The kinetic study indicated that the degradation process tended to follow pseudo-first-order kinetics. These findings demonstrate that TiO₂/Biochar has strong potential as an effective photocatalyst for tartrazine degradation in wastewater treatment.